Penguatan Kompetensi Lulusan SMK Kota Cirebon Melalui Pelatihan Junior Network Administrator - Irfan Ali; Kaslani; Sri Ayuningsih; Firda Pardiana (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In today's increasingly advanced digital era, the need for skilled personnel in network administration is growing. This Community Partnership Program aims to provide junior network administrator training for graduates of Vocational High Schools (SMK) in Cirebon City. This training is designed to equip participants with essential basic knowledge and skills in managing and maintaining computer network infrastructure. The material presented includes basic network concepts, network device configuration, fundamental network security principles, and common troubleshooting techniques. It is hoped that this program can enhance the competence of SMK graduates, making them more prepared to enter the workforce in the field of information technology.